Development of a Cowpea Immature Pod Purée: An Opportunity for the Elderly to Improve Their Autonomy in Daily Living Activities and Quality of Life - Catarina Passão; Alfredo Aires; Miguel Rodrigues; Luís Ferreira; Irene Gouvinhas; Ana Barros (Medical Sciences Forum, 2022)
The nutritional composition of cowpea (Vigna unguiculata (L.) Walp.) has been related to the prevention of diverse metabolic and cardiovascular diseases. Previous works have shown that cowpea immature pods exhibited higher phenolic composition and antioxidant activity as compared to immature and dry seeds. This work aims to develop a cowpea immature pod ready-to-eat purée for the elderly to promote the maintenance of their muscle mass and synthesis of neurotransmitters implicated in depression disorder and sleep quality. In a preliminary approach, this study intends to assess the phenolic content, antioxidant capacity, nutritional composition, and essential and non-essential amino acids of the cowpea at two different growth stages: immature pods and green seeds. Immature pods showed a significantly higher content of total phenols (11.73 ± 0.43 mg AG/g dry weight), ortho-diphenols (13.18 ± 1.26 mg GA/g dw), and flavonoids (6.04 ± 0.51 mg CAT/g dw) as compared to the green seeds. The higher antioxidant capacity was also displayed by the pods (ABTS•⁺ (2-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) radical): 0.05 ± 0.00 mmol Trolox/g dw, DPPH• (2,2-diphenyl-1-picrylhidrazyl radical): 0.04 ± 0.00 mmol Trolox/g dw, FRAP (Ferric Reduction Antioxidant Power): 0.04 ± 0.00 mol Trolox/g dw) in contrast with the green seeds. Immature pods demonstrated the lowest crude fat content (1.74 ± 0.03%) and the highest content of crude protein (27.48 ± 1.05%) and of insoluble dietary fibre (35.63 ± 0.53%). To our knowledge, we present the first study concerning the nutritional composition of cowpea immature pod, suggesting that it has remarkable potential to be included in the development of a new functional food product for the elderly.